PERSEPSI WISATAWAN TERHADAP POTENSI OBJEK WISATA PANTAI SOPAPEI DESA SULI KABUPATEN MALUKU TENGAH - Maitha Monita Kaihatu; Lilian Sarah Hiariey (Universitas Pattimura, 2021)
ABSTRACTSopapei Beach has the potential to be developed and plays a role in tourism development. This can be seen from the white sand, clear sea water and a very comfortable atmosphere that can be enjoyed when entering the Sopapei Beach. The development of the Sopapei Beach tourism object is expected to provide input for the development of Sopapei Beach tourism to attract more tourists to visit. Tourist ratings of existing tourist objects can be used as a reference for the development of tourism objects in the future. The purposes of this study were to describe the existing potential of the Sopapei Beach tourism object and to analyze the visitor's perception of the Sopapei Beach tourist attraction. Descriptive and perception analyses were used to describe tourists' perceptions of the Sopapei Beach tourism. The results showed that the attractiveness of the Beach has its own features compared to other tourist objects in Central Maluku Regency, in terms of having a shady and quiet beach, a very sloping beach location on the edge of the sea, beautiful scenery, clear water and a special feature as well. When tide is far away, it is suitable for tourist who wants a calm atmosphere to release their fatigue from busy work activity. In the perception of tourist attraction in the Sopapei Beach, the surrounding community is always involved in environmental cleaning activities and maintaining the comfort and safety of the Sopapei Beach tourist attraction, indicated by the percentage values of convenience by 96% and of the safety 98%.